Deciphering the resistance mechanism to Fusarium wilt and stem rot of Passiflora maliformis var. pubescens using histopathology aspects - Galvis-Tarazona, Daicy; Bohórquez-Quintero, María; Arias-Moreno, Diana; Ojeda-Pérez, Zaida (Frontiers in Plant Science, 2025)
IntroductionPassiflora maliformis is a wild genotype of passionflower with antimicrobial activity and broad phytochemical properties, highlighting its potential as a genetic resource for crop improvement. Given that commercial passionflowers are severely affected by vascular wilt and stem rot caused by Fusarium oxysporum and F. solani, this study aimed to elucidate the resistance mechanisms of P. maliformis var. pubescens against these pathogens, with emphasis on histopathological aspects.MethodsPathogenicity tests were performed on seedlings germinated in vitro and ex vitro (SI and SE). Survival, disease incidence, and severity were evaluated in inoculated and non-inoculated plants. In addition, histopathological analyses of roots and stems were performed to characterize structural changes, defense responses, and pathogen colonization.ResultsThe genotype exhibited high survival rates and reduced incidence and severity of Fusarium wilt and stem rot, with minimal damage to internal and external tissues. Comparable shoot and root development was observed between inoculated and control plants, indicating the effectiveness of defense mechanisms that maintained physiological performance. Histopathological examination revealed reinforced cell walls, limited pathogen penetration, and restricted vascular colonization.ConclusionP. maliformis var. pubescens demonstrated high responsiveness against F. oxysporum and F. solani, supporting their role as a potential resistant rootstock. These findings underscore the value of this wild genotype as a strategic genetic resource for breeding programs, integrated disease management, and the sustainable improvement of commercial passionflower crops.